2006
DOI: 10.1111/j.1467-6427.2006.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Six things worth understanding about psychoanalytic psychotherapy

Abstract: This paper is written for family therapists who may be curious but sceptical about psychoanalysis and psychoanalytic psychotherapy. It examines a number of areas of misunderstanding within mainstream family therapy discourse (diversity, authoritarianism, terminology, blame, history and separation) which, the author believes, have acted to help maintain a false coherence for family therapy through a distorted construction of the otherness of psychoanalytic therapy and, in so doing, inhibited a potentially more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…In this context, contributions of both object-relational psychodynamic approaches (e.g. Dare, 1998;Donovan, 2003;Flaskas, 1997;Gerson, 1996;Kaslow, 2001;Pocock, 2006) as well as the related attachment paradigm (Akister and Reibstein, 2004;Byng-Hall, 1997;Clulow, 2001;Kozlowska and Hanney, 2002) have been extensively discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, contributions of both object-relational psychodynamic approaches (e.g. Dare, 1998;Donovan, 2003;Flaskas, 1997;Gerson, 1996;Kaslow, 2001;Pocock, 2006) as well as the related attachment paradigm (Akister and Reibstein, 2004;Byng-Hall, 1997;Clulow, 2001;Kozlowska and Hanney, 2002) have been extensively discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The method was inspired by Frank (1970) who suggested that therapists need theories as a secure base for their work – enabling them to ‘explain and guide their interventions’ (p.148). Since then, the imperative to find the objectively ‘right’ model has been challenged by postmodernism and social constructionism (Pocock, 2006); the emphasis is now on usefulness, and allows a ‘universe’ of models (cf. Parry, 1991).…”
Section: Rationalementioning
confidence: 99%
“…We were aware that current PPD practice often failed to offer some trainees the chance to consider in more depth the experiences they bring to being a therapist (Hildebrand, 1998). Moreover, as family therapy has become more comfortable about borrowing ideas from insight‐driven traditions of therapy (Pocock, 2006) and is influenced by integrative developments in contemporary psychological therapies in general, in which greater importance is given to the role of common factors in therapeutic tradition, a stronger role for training the self of the therapist has become more relevant (Eisler, 2006; Simon, 2007; Sexton, 2007; Sprenkle and Blow 2004, 2007). These influences explain why contemporary training must foreground the self of the therapist rather than the techniques of the therapist.…”
Section: Rationalementioning
confidence: 99%